Hahaha - Liucci-Goutnikov, Nicolas (Paris : Éditions Skira : Éditions du Centre Pompidou, 2021)
From the caricatures of Honoré Daumier, to the ready-mades of Marcel Duchamp, the puns of the Dadas, the videos of Dalí, to the works of John Baldessari and Marcel Broodthaers, humour has been a powerful tool in art, especially to be critical of itself. This catalogue will explore the humour of art through its different variations: toys and games, hoaxes, puns, jesters... A humorous essay by curator Nicolas Liucci- Gutnikov introduces the subject. An anthology of philosophical and historical texts puts humour as a tool of criticism in context, from Pascal, Montaigne, to Baudelaire and Nietzsche... Finally, some humorous quotes Dada and surrealist artists and writers punctuate the book. [provided by publisher]
Hahaha, ING Art Center, Brussel, 15 september 2021 tot 16 januari 2022
boek